Iron limitation of kelp growth may prevent ocean afforestation - Ellie R. Paine; Philip W. Boyd; Robert F. Strzepek; Michael Ellwood; Elizabeth A. Brewer; Guillermo Diaz-Pulido; Matthias Schmid; Catriona L. Hurd (Communications Biology, 2023)
Abstract Carbon dioxide removal (CDR) and emissions reduction are essential to alleviate climate change. Ocean macroalgal afforestation (OMA) is a CDR method already undergoing field trials where nearshore kelps, on rafts, are purposefully grown offshore at scale. Dissolved iron (dFe) supply often limits oceanic phytoplankton growth, however this potentially rate-limiting factor is being overlooked in OMA discussions. Here, we determine the limiting dFe concentrations for growth and key physiological functions of a representative kelp species, Macrocystis pyrifera, considered as a promising candidate for OMA. dFe additions to oceanic seawater ranging 0.01-20.2 nM Fe′ ‒ Fe′ being the sum of dissolved inorganic Fe(III) species ‒ result in impaired physiological functions and kelp mortality. Kelp growth cannot be sustained at oceanic dFe concentrations, which are 1000-fold lower than required by M. pyrifera. OMA may require additional perturbation of offshore waters via dFe fertilisation.